2017
DOI: 10.1016/j.scitotenv.2016.11.092
|View full text |Cite
|
Sign up to set email alerts
|

A novel integrated modelling framework to assess the impacts of climate and socio-economic drivers on land use and water quality

Abstract: Changes in climatic conditions will directly affect the quality and quantity of water resources. Further on, they will affect them indirectly through adaptation in land use which ultimately influences diffuse nutrient emissions to rivers and therefore potentially the compliance with good ecological status according to the EU Water Framework Directive (WFD). We present an integrated impact modelling framework (IIMF) to track and quantify direct and indirect pollution impacts along policy-economy-climate-agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 51 publications
0
17
0
3
Order By: Relevance
“…Anthropogenic-related drivers such as population growth (Geist et al 2006;Meshesha et al 2014), urbanization (d'Amour et al 2017Wang et al 2016;Yirsaw et al 2017), agricultural expansion (Ramankutty et al 2006;Mustard et al 2012), pasturing (Wassenaar et al 2007), and global market forces (Lambin & Meyfroidt 2011;Lambin et al 2003) are among the known drivers of LULCC. Besides such basic human-related drivers, recent studies indicated that climate change vulnerability has a significant forcing effect on LULCC (Biazin & Sterk 2013;Kindu et al 2015;Lambin et al 2003;Reid et al 2000;Zessner et al 2017). This could be possible through its direct effect, for example, the effect of recurrent drought on land cover and crop productivity (Ravindranath & Sathaye 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic-related drivers such as population growth (Geist et al 2006;Meshesha et al 2014), urbanization (d'Amour et al 2017Wang et al 2016;Yirsaw et al 2017), agricultural expansion (Ramankutty et al 2006;Mustard et al 2012), pasturing (Wassenaar et al 2007), and global market forces (Lambin & Meyfroidt 2011;Lambin et al 2003) are among the known drivers of LULCC. Besides such basic human-related drivers, recent studies indicated that climate change vulnerability has a significant forcing effect on LULCC (Biazin & Sterk 2013;Kindu et al 2015;Lambin et al 2003;Reid et al 2000;Zessner et al 2017). This could be possible through its direct effect, for example, the effect of recurrent drought on land cover and crop productivity (Ravindranath & Sathaye 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This could be possible through its direct effect, for example, the effect of recurrent drought on land cover and crop productivity (Ravindranath & Sathaye 2002). Climate change could also indirectly affect LULCC by increasing the demand for more croplands and by forcing climate change vulnerable communities to adjust their land use choices in order to cope up with such changes (Messina et al 2014;Zessner et al 2017). This is particularly true in developing countries where agriculture is the backbone of the economy.…”
Section: Introductionmentioning
confidence: 99%
“…increasing the mineralisation of organic matter, decreasing oxygen solubility, increasing the variability in pH values and increasing growth rates of aquatic organisms. A lower water availability might affect the quality of surface water resources adversely and even have a significant negative impact on human health and the economic development of the entire region [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The facts show that effects of climate change have not been properly addressed in policy formulation and water resource management strategies in many regions around the world, probably due to the lack of accurate and reliable data on the possible effects of climate change on water resources. Nitrogen pollution is already considered as a global problem [11], and it is expected that N loss will aggravate in vulnerable areas due to climate change [5,8]. For this, it is of upmost importance to assess and quantify the impacts of climate change and vulnerability of water resources and evaluate the efficiency of possible adaptation and mitigation policies.…”
Section: Introductionmentioning
confidence: 99%
“…Bockstael et al, 1995;Volk et al, 2008;Marta-Costa et al, 2013;Cordier et al, 2017;Zessner et al, 2017).…”
Section: Introductionunclassified